Examination of Social Studies Textbooks in terms of Approaches of Values Education - (:unkn) unknown (EDAM, 2012)
In the program of primary education in Turkey, comprehensive modifications were made by the Ministry of Education and The Chairman of the Board of Education (TTKB) in 2004. In this new Social Study and Instruction program some values Like assiduity, scientificity, responsibility and respect to variety are defined as the value given direct. The target of this study is to examine these activities which take part in the lesson books of social studies at 6th grade and 7th grade in terms of approaches of values education. Five social studies lesson books of 6th grade and three social studies lesson books of 7th grade which received approval from The Chairman of The Board of Education (TTKB) in the 2010-2011 academic years compose the universe of this study which executed with the examination method. Two social studies lesson books of 6th and 7th class which are chosen randomly among these books constitute the sampling of this study. In order to determine that if these activities are suitable to the approaches of values education, a Schedule of Event Criteria (SEC) is improved by the researchers and the data are examined according to this schedule. As a result of this examination in these activities for values of education which take part in social studies lesson books of 6th and 7th grade, some findings are reached that approaches of value analysis and suggestion are given in but moral reasoning, explanation of value, observation/learning through modeling are not given in.
Keywords: Social Studies; Examination of Lesson Book; Values of Education; Approaches of Values Education